Facile solvothermal designing of graphene/Ni3V2O8 nanocomposite as electrode for high performance symmetric supercapacitor - Low, Wei Hau; Khiew, Poi Sim; Lim, Siew Shee; Chiu, Wee Siong; Ezeigwe, Ejikeme Raphael (Elsevier, 2018)
In the present study, graphene/Ni3V2O8 nanocomposites were successfully synthesised by a facile solvothermal approach in which the graphene sheets were fabricated via the environmentally benign liquid phase exfoliation with optimised ethanol to water volume ratio (2:3). The nanocomposites integrated separately the advantages of graphene sheet and pseudocapacitive nature of Ni3V2O8 and hence possessed electrochemical performance which outperformed the pristine Ni3V2O8. Optimizations on the weight ratio between the graphene and Ni3V2O8 were performed to determine the synergistic effect between the highly conductive graphene sheet and Ni3V2O8. Among the graphene/Ni3V2O8 nanocomposites, G-4NVO (graphene/Ni3V2O8 with the weight ratio of 1:4) was proved to be a promising electrode material, as it delivered eminent specific capacitance of 748 Fg−1 at current density of 0.5 Ag-1, remarkable energy density of 103.94 Wh/kg at power density of 45.61 kW/kg, reasonable cycling stability with 71% capacitance retention and superior coulombic efficiency of 83% after 3000 charge-discharge cycles at 0.5 Ag-1.